2010
DOI: 10.1088/0964-1726/19/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

Improving electrochromic properties via copolymerization

Abstract: Copolymers of 5,8-di(1H-pyrrol-2-yl)-2,3-di(thiophen-2-yl)quinoxaline (PTQ) in the presence of 2,2 -bis(3,4-ethylenedioxythiophene) (BiEDOT) and 4,7-bis (2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)-2-dodecyl-2H-benzo[1,2,3] triazole (BEBT) were synthesized via the potentiodynamic method in a tetrabutylammonium perchlorate/dichloromethane (TBAP/DCM) (0.1 M) solvent-electrolyte couple. P(PTQ-co-BiEDOT) reveals an oxidation potential at +0.45 V and a reduction potential at −0.2 V (figure 1(a)), whereas the homopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…19 Monomer of compound 19, 4,7-bis(2,3-dihydrothieno [3,4-b] [1,4]dioxin-5-yl)-2-dodecyl-2H-benzo [1,2,3] triazole (BEBT), was used as the comonomer against benzoquinoxaline and pyrrole bearing ones and it has been shown that copolymerization with BEBT increases the optical and kinetic properties of the resulting polymer even more efficiently than simple copolymerization with Bi-EDOT. 20,21 Benzazole-EDOT bearing DA type ECPs, 14 and 15, revealed a green color in their neutral states accompanied by highly transmissive oxidized states. 22,23 They showed two p-p* transitions which was claimed as essential to obtain green colored polymers.…”
Section: Electrochromics (Ecs)mentioning
confidence: 99%
“…19 Monomer of compound 19, 4,7-bis(2,3-dihydrothieno [3,4-b] [1,4]dioxin-5-yl)-2-dodecyl-2H-benzo [1,2,3] triazole (BEBT), was used as the comonomer against benzoquinoxaline and pyrrole bearing ones and it has been shown that copolymerization with BEBT increases the optical and kinetic properties of the resulting polymer even more efficiently than simple copolymerization with Bi-EDOT. 20,21 Benzazole-EDOT bearing DA type ECPs, 14 and 15, revealed a green color in their neutral states accompanied by highly transmissive oxidized states. 22,23 They showed two p-p* transitions which was claimed as essential to obtain green colored polymers.…”
Section: Electrochromics (Ecs)mentioning
confidence: 99%
“…134 The polymer possessed 66% optical contrast in the near IR region with a switching time of 1.2 s. Subsequently, the copolymer of (35) with BiEDOT was synthesized. 135 The resulting polymer had a l max at 525 nm (E g ¼ 1.4 eV) with a purple color in neutral state. The copolymer achieved 10% optical contrast around 2 s in the visible range.…”
Section: Structural Modicationmentioning
confidence: 99%
“…Polymer electrochromic (PEC) materials have received extensive attention due to their wide variety of structures, rich color range, high optical contrast, good processability, adjustable band, and fast response and are considered as one of the development directions for the next generation of EC materials. At present, the multicolor display properties of PEC materials are generally achieved through molecular structure design and modification such as donor–acceptor (D–A) structure design and the copolymerization of different monomers. Copolymerization is an effective structural adjustment method that can combine the advantages of two or more monomers to improve the electrochromic properties of polymers. , We have used copolymerization to synthesize a series of multicolor display polymer materials. However, the randomness of the copolymerization is not conducive to the in-depth study of the relationship between the molecular structure and the discoloration properties of the PEC material.…”
Section: Introductionmentioning
confidence: 99%